2015
DOI: 10.1534/genetics.115.178137
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Drift and the Evolutionary Dynamics of Dosage-Sensitive Duplicate Genes

Abstract: Dosage-balance selection preserves functionally redundant duplicates (paralogs) at the optimum for their combined expression. Here we present a model of the dynamics of duplicate genes coevolving under dosage-balance selection. We call this the compensatory drift model. Results show that even when strong dosage-balance selection constrains total expression to the optimum, expression of each duplicate can diverge by drift from its original level. The rate of divergence slows as the strength of stabilizing selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 68 publications
0
66
0
Order By: Relevance
“…Our results also demonstrated that genes showing significant HSE largely overlapped between populations and these genes were not strongly enriched for GO terms. These genes probably evolve under a compensatory drift model (58). This was evident in the direction of the HSE, which was the same in all accessions.…”
Section: Neutral Inter-population Expression Differencesmentioning
confidence: 79%
“…Our results also demonstrated that genes showing significant HSE largely overlapped between populations and these genes were not strongly enriched for GO terms. These genes probably evolve under a compensatory drift model (58). This was evident in the direction of the HSE, which was the same in all accessions.…”
Section: Neutral Inter-population Expression Differencesmentioning
confidence: 79%
“…It is also possible that regulatory mutations first silence one duplicate copy, opening the way to its neutral degeneration (Thompson et al 2016). The neutral evolution of asymmetric expression levels between duplicate copies has indeed been reported (Gout and Lynch 2015;Lan and Pritchard 2016;Thompson et al 2016). But (i) this process was shown to require substantial amounts of time, and (ii) the evolution of expression levels in the nervous system is tightly controlled and slower than in other tissues (Pennacchio et al 2006;Brawand et al 2011;Barbosa-Morais et al 2012;Merkin et al 2012).…”
Section: /46mentioning
confidence: 99%
“…A possible explanation for this trend is that while the duplication of a single subunit of a complex may be deleterious by perturbing stoichiometry, duplication of all subunits at once may not cause such disadvantage since balance is preserved (Birchler and Veitia, 2012;Rice and McLysaght, 2017). Another possibility is that WGDs are maintained due to their dosage effects, which results in selection for the maintenance of their protein function (Gout and Lynch, 2015;Thompson et al, 2016) and at the same time favors the maintenance of HET complexes.…”
Section: Discussionmentioning
confidence: 99%